Assessment of the knowledge of female students of the Medical University of Warsaw regarding the prevention of HPV infections - Kalita-Kurzyńska, Kinga; Duda-Zalewska, Aneta (Nursing in the 21st Century, 2022)
ASSESSMENT OF THE KNOWLEDGE OF FEMALE STUDENTS OF THE MEDICAL UNIVERSITY OF WARSAW REGARDING THE PREVENTION OF HPV INFECTIONS Introduction. According to the WHO, the health consequences of HPV infections constitute a serious public health problem. In order to avoid HPV infections, the primary prevention, mainly vaccination, plays a crucial role. Aim. The aim of the study is an assessment of the knowledge about HPV infection prevention of female students from diff erent degree courses at the Medical University of Warsaw. Material and methods. The study was conducted among 181 female students who studied one of three degree courses: nursing, midwifery and public health, using a diagnostic survey. The tool of the study was the author’s questionnaire. The independence test χ² was used for statistical analysis. The statistical signifi cance was assumed to be: p <0.05. The calculations were performed in Microsoft Excel and SPSS. Results. All the female students correctly explained the abbreviation ”HPV”. The midwifery students answered more often than other students that the HPV oncogenic types, which cause cervical cancer, are type 16 and type 18. The nursing students, more often than the midwifery and public health students, knew that barrier contraception reduces the chance of infection, but does not completely eliminate it. The knowledge about HPV vaccine prophylaxis did not depend on the degree course. Conclusions. The surveyed students have suffi cient knowledge on the prevention of HPV infections, and also use reliable sources of information. The knowledge acquired by the respondents is based on current scientifi c reports and therefore they are prepared to undertake educational activities.